2014
DOI: 10.1093/schbul/sbu153
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-striatal Dysfunction During Reward Processing in Unaffected Siblings of Schizophrenia Patients

Abstract: Schizophrenia is a psychiatric disorder that is associated with impaired functioning of the fronto-striatal network, in particular during reward processing. However, it is unclear whether this dysfunction is related to the illness itself or whether it reflects a genetic vulnerability to develop schizophrenia. Here, we examined reward processing in unaffected siblings of schizophrenia patients using functional magnetic resonance imaging. Brain activity was measured during reward anticipation and reward outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
57
4

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 82 publications
(123 reference statements)
16
57
4
Order By: Relevance
“…However, other studies have suggested that type 2 bipolar disorder and adolescent bipolar disorder are associated with frontostriatal BOLD signal during reward anticipation [47][48][49] and that relatives of patients with schizophrenia have increased VS BOLD during reward receipt. 19 In line with the meta-analysis, 12 the most prominent association between psychosis RPS and VS BOLD occurred during the reward anticipation phase, suggesting that risk for psychosis may alter disrupt incentive motivation and reward salience. The receipt phase could also be less sensitive to VS activation (because of variable success rates), which could explain the weaker association with the psychosis RPS.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…However, other studies have suggested that type 2 bipolar disorder and adolescent bipolar disorder are associated with frontostriatal BOLD signal during reward anticipation [47][48][49] and that relatives of patients with schizophrenia have increased VS BOLD during reward receipt. 19 In line with the meta-analysis, 12 the most prominent association between psychosis RPS and VS BOLD occurred during the reward anticipation phase, suggesting that risk for psychosis may alter disrupt incentive motivation and reward salience. The receipt phase could also be less sensitive to VS activation (because of variable success rates), which could explain the weaker association with the psychosis RPS.…”
Section: Discussionsupporting
confidence: 54%
“…1 We recently found that a schizophrenia RPS was associated with an attenuated VS BOLD response during a probabilistic learning task, 15 suggesting that the cumulative effect of risk single-nucleotide polymorphisms was associated with the VS BOLD alterations previously observed in patients with psychosis [16][17][18] and unaffected relatives. 19 However, it is currently not known whether polygenic risk of psychotic disorders is associated with reward processes, such as anticipation and receipt, as assayed using the monetary incentive delay (MID) task. 20 The MID task assays BOLD during incentive processing and is relatively independent of reward-based learning (participants learn the stimulusreward associations before scanning) 21 compared with probabilistic learning paradigms, which assay an individual's ability to dynamically update assumptions based on choice behavior and outcomes.…”
mentioning
confidence: 99%
“…Consequently, altered frontostriatal white matter organization may represent a genetic vulnerability for schizophrenia. Such an interpretation is in line with other observations of impaired frontostriatal dysfunction in firstdegree relatives of schizophrenia patients (Grimm et al, 2014;de Leeuw et al, 2013de Leeuw et al, , 2015bRaemaekers et al, 2006;Vink et al, 2006;Zandbelt et al, 2011).…”
Section: Introductionsupporting
confidence: 91%
“…Moreover, these regions are key components of the reward network (McClure et al, 2004;Sesack and Grace, 2010). We and other have reported on changes in frontostriatal reward processing in schizophrenia patients (Morris et al, 2012;Nielsen et al, 2012), siblings (Grimm et al, 2014;de Leeuw et al, 2015b), and offspring (Vink et al, 2016b).…”
Section: Discussionmentioning
confidence: 88%
“…Compared to healthy controls (HCs), differences in ventral striatal activity were observed in studies in patients with first-episode schizophrenia (FEP-SZ) and first-degree relatives of patients with schizophrenia. [15][16][17][18] Other studies including patients with broadly defined first-episode psychosis (not restricted to schizophrenia and schizophreniform disorder) or individuals at-risk for psychosis did not report any group differences, but focused more on the relationship with symptom expression. [19][20][21][22][23] This work supports the idea that on a group level reduced activation of the striatum may be more strongly related to schizophrenia or chronic forms of psychosis than to psychotic disorders in general.…”
Section: Introductionmentioning
confidence: 99%